2019
DOI: 10.1111/ene.13895
|View full text |Cite
|
Sign up to set email alerts
|

Early‐morning OFF and levodopa dose failures in patients with Parkinson's disease attending a routine clinical appointment using Time‐to‐ON Questionnaire

Abstract: Background and purpose In patients with Parkinson's disease (PD) with motor fluctuations, total daily OFF time is comprised of both end‐of‐dose time and the time taken to turn ON with medication. However, little is known about the impact of delays in ON time. Methods This was a single‐visit pilot study of fluctuating patients with PD attending a routine appointment. During a single visit, adult patients with idiopathic PD who were treated with levodopa for at least 1 year completed a questionnaire evaluating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…In our study, patients recognized morning akinesia to a greater extent than physicians, with 58.7% of patients reporting morning akinesia compared with 48.9% of physicians (Table 2). This nding is in line with the results of an Italian survey in 151 consecutive patients, which reported that 64.2% of patients were able to recognize morning akinesia [21]. Taken together, these ndings suggest that patients easily recognize the presence of morning akinesia and are therefore more likely to discuss any concerns with their physicians [19].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, patients recognized morning akinesia to a greater extent than physicians, with 58.7% of patients reporting morning akinesia compared with 48.9% of physicians (Table 2). This nding is in line with the results of an Italian survey in 151 consecutive patients, which reported that 64.2% of patients were able to recognize morning akinesia [21]. Taken together, these ndings suggest that patients easily recognize the presence of morning akinesia and are therefore more likely to discuss any concerns with their physicians [19].…”
Section: Discussionsupporting
confidence: 88%
“…The primary goal of 24-h LCIG treatment is to reduce nocturnal fluctuations in motor symptoms and NMS and improve quality of sleep. Patients may benefit from 24-h LCIG administration if they experience noteworthy wearing off of symptoms overnight, delayed morning latency (i.e., delayed time to "on" following the first morning levodopa dose) [34], insomnia, stiffness, tremor, or dystonia due to wearing off of symptoms overnight, severe night-time akinesia or bradykinesia, severe night-time pain, and/or severe night-time urinary problems. Because of the limited evidence regarding 24-h LCIG infusion, the initiation of 24-h treatment should be decided individually, after weighing the potential benefits and drawbacks.…”
Section: Patients Who May Benefit From 24-h Lcig Usementioning
confidence: 99%
“…Stocchi et al reported that the majority of PD patients with motor fluctuations also suffered from delays in ON time (latency > 30 min) following their first morning dose of L-dopa. [7]. However, some patients can experience an improvement of symptoms in the morning.…”
Section: A Long Day For a Patient With Pdmentioning
confidence: 99%